PENGARUH SUKU BUNGA KREDIT DAN INFLASI TERHADAP PERMINTAAN KREDIT PADA BANK PERKREDITAN RAKYAT DI INDONESIA - B01109116, Jona Amanda P (Jurnal Pembangunan dan Pemerataan, 2013)
The title of this research is "The Effect of Interest Rate and Inflation Against Credit Demand of Rural Banks in Indonesia", that have aims to "identify and analyze the effect of working capital loan interest rates and inflation on the demand for working capital loans to the rural banks in Indonesia, identify and analyze the effect of interest rates and inflation on investment credit demand in rural banks in Indonesia and to identify and analyze the effect of interest rates and inflation on consumer credit loan demand in rural banks in Indonesia ". The exact method to test this relationship is multiple linear regression method, using secondary data obtained from Bank Indonesia publications. Based on the results of data processing that has seen from the t test, I obtained the results of the working capital loan interest rates and inflation are significantly and negatively related to the demand for working capital loans to the rural banks in Indonesia, the investment loan interest rates and inflation significantly and negatively related to the demand for investment credit and consumer credit at rural bank in Indonesia and consumer lending and significant negative effect on consumer credit demand but inflation is negative and significant effect on demand for consumer credit in rural banks in Indonesia. Keywords: Interest Rate, Inflation and Credit Demand BPR